“Putting Science into Action”: A Case Study of How an Educational Intermediary Organization Synthesizes and Translates Research Evidence for Practice - Metzger, Ashley; Duane, Addison; Nash, Amia; Shapiro, Valerie (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2024)
Background: Knowledge brokering by intermediary organizations includes knowledge distillation processes (e.g., synthesis, translation).Aims and objectives: This article explores how an educational intermediary performs research distillation when creating virtual knowledge reservoirs for educators.Methods: The authors use qualitative data from semi-structured interviews, coded to consensus, and thematically analyzed.Findings: During synthesis, intermediaries apply a “research lens” to evaluate the credibility of the evidence. During translation, they rely on their experience as educators to share evidence in a non-academic voice and generate “turnkey” strategies.Discussion and conclusion: The article considers the knowledge brokering pipeline fallacy and examines the potential of ongoing processes for improving the effectiveness of intermediaries with the aim of diminishing research-practice and research-policy gaps in education.